2020
DOI: 10.2337/dc19-2006
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure Treatment, Glycemia, and Diabetes Risk in Obstructive Sleep Apnea and Comorbid Cardiovascular Disease

Abstract: Despite evidence of a relationship among obstructive sleep apnea (OSA), metabolic dysregulation, and diabetes, it is uncertain whether OSA treatment can improve metabolic parameters. We sought to determine effects of long-term continuous positive airway pressure (CPAP) treatment on glycemic control and diabetes risk in patients with cardiovascular disease (CVD) and OSA. RESEARCH DESIGN AND METHODSBlood, medical history, and personal data were collected in a substudy of 888 participants in the Sleep Apnea cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 33 publications
0
30
1
Order By: Relevance
“…In another controlled study, assessing the effect of 6‐month PAP therapy on HbA1c in 26 patients with sub‐optimally controlled diabetes and OSA, PAP significantly improved glycaemic control (Martínez‐Cerón et al., 2016). In contrast to previous studies, long‐term CPAP in addition to usual care in OSA patients with manifest cardiovascular diseases was not associated with improved glycaemic control in those with diabetes, or prevention of new diabetes diagnoses, compared with usual care alone (Loffler et al., 2020). However, this sub‐analysis within the SAVE study included a less symptomatic subpopulation of OSA that may be significantly different from the group of studies included in the current ESADA cohort reflecting a reference patient cohort referred to tertiary sleep centres.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In another controlled study, assessing the effect of 6‐month PAP therapy on HbA1c in 26 patients with sub‐optimally controlled diabetes and OSA, PAP significantly improved glycaemic control (Martínez‐Cerón et al., 2016). In contrast to previous studies, long‐term CPAP in addition to usual care in OSA patients with manifest cardiovascular diseases was not associated with improved glycaemic control in those with diabetes, or prevention of new diabetes diagnoses, compared with usual care alone (Loffler et al., 2020). However, this sub‐analysis within the SAVE study included a less symptomatic subpopulation of OSA that may be significantly different from the group of studies included in the current ESADA cohort reflecting a reference patient cohort referred to tertiary sleep centres.…”
Section: Discussioncontrasting
confidence: 86%
“…In another controlled study, assessing the effect of 6-month PAP therapy on HbA1c in 26 patients with sub-optimally controlled diabetes and OSA, PAP significantly improved glycaemic control (Martínez-Cerón et al, 2016). In contrast to previous studies, long-term CPAP in addition to usual care in OSA patients with manifest cardiovascular diseases was not associated with improved glycaemic control in those with diabetes, or prevention of new diabetes diagnoses, compared with usual care alone (Loffler et al, 2020).…”
Section: Osa Treatment and Glycaemic Healthmentioning
confidence: 83%
“…HbA1c is a measure of glucose levels during the last 2–3 months, which takes time to change ( 18 ). A randomized clinical trial investigated the long-term effect of PAP on glycemic control in 888 patients with OSA and stable cardiovascular disease ( 40 ). In those with pre-existing DM2 ( n = 274, 31%) and prediabetes ( n = 452, 51%), there was no significant difference between the PAP and usual care groups in HbA1c during follow-up (median duration 4.3 years) ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides evidence more time spent undertaking MVPA was associated with lower odds of severe OSA, and less severe hypoxaemia. Importantly, whilst CPAP is effective at eliminating hypoxaemia [ 40 ], cardiovascular and metabolic health problems still remain in patients with OSA [ 9 , 10 ]. Therefore, the results of this study, when coupled with the well-established benefits of MVPA on other health conditions [ 11 13 ], suggest that MVPA should be prescribed for all patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…R otenburg et al [ 8 ] showed that for each year over a 20-year period (1994–2015), up to 40% of CPAP users were “non-compliant”. Furthermore, recent large randomised controlled trials have demonstrated that CPAP does not reduce the chances of a secondary cardiovascular or cerebrovascular event [ 9 ], nor improve glycaemic control of type 2 diabetes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%